On eddy polarity distribution in the southwestern Atlantic - Saraceno, Martin (2012)
Eddies in the southwestern Atlantic were detected from more than 18 years of satellite altimetry data using a modified version of the Okubo–Weiss method. The spatial distribution and polarity of eddies were examined. A larger concentration of cyclonic (anticyclonic) eddies was found on the left (right) side when looking downstream on some of the largest current systems in the region, such as the South Atlantic Current, the anticyclonic circulation associated with the Zapiola Drift (ZD) and the northern branch of the Antarctic Circumpolar Current. In the region isolated by the anticyclonic Zapiola Current, 91% of eddies were cyclonic. The observed distribution of eddies is in agreement with the generation of eddies from meanders of the above-mentioned currents: cyclonic (anticyclonic) eddies might detach from a meander of the current on the left (right) side when looking downstream on the current. Furthermore, in the ZD area, the bottom topography plays a key role in determining the trajectory of eddies: the anticyclonic current associated with the ZD meanders and eventually generates a cyclonic eddy that enters the ZD region only across the northeastern border, where the gradient of potential vorticity is lower. Finally, average surface chlorophyll-a concentration inside cyclonic and anticyclonic eddies shows that the former have higher chlorophyll-a values. Thus, on average, the classical eddy-pumping theory explains the difference in chlorophyll-a concentration within eddies in the southwestern Atlantic.